Histological changes following epidural injection of midazolam in the neonatal rabbit - (:unkn) unknown (ARNETTE-BLACKWELL S A, 1997)
Midazolam can produce antinociceptive effects when used via intrathecal or epidural routes. Neurotoxicity studies are scanty especially for neonates. The aim of this study was to carry out electron microscopic (EM) examinations in the neonatal rabbit to determine the histological effects of epidural midazolam on spinal cord. Twenty white New Zealand neonatal rabbits were randomly assigned to three groups receiving single dose of 0.9% saline (Group I; Control, n = 4), 0.9% saline titrated to pH = 3.9 by addition of hydrochloric acid (Group II; n = 6), midazolam 250 mu g.kg(-1) (Group III; n = 12) epidurally. Half of each group were sacrificed on the second day and the remainder on the seventh day and spinal cord sections were evaluated by EM. Control group displayed normal histology on grids. Group II and II showed a variable degree of neurotoxic effects such as degeneration of vacuoles, cytoplasm and neurofilaments, disruption of myelin sheaths, lysis of cell membranes, perivascular oedema, pyknosis of nuclei. The toxic effects of acidic saline and midazolam are similar, in view of these results the epidural use of acidic midazolam (commercially available preparations) in neonates should be avoided.
Keywords: neonate; analgesic technique, epidural; midazolam, neurotoxicity; INTRATHECAL MIDAZOLAM; MORPHINE; NEUROTOXICITY; CHILDREN; INFANTS; MONKEYS; DOGS